Alcoholic Cardiomyopathy: a summary of current knowledge and possible future directions - Górny, Aleksander; Wójcik, Anna; Chwiejczak, Justyna; Obrębski, Michał; Kościan, Jan; Młynarska, Julita; Langa, Jakub; Szczerkowska, Karolina; Seroka, Anna; Rybicka, Maria (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Ethanol is still one of the most frequently consumed drugs worldwide and is a strong risk factor for more than 60 illnesses including alcoholic cardiomyopathy which is a specific heart muscle disease caused by long-term excessive alcohol consumption. The review aims to gather available data and summarize it to give better understanding of the disease, to help select patients with the condition to implement proper treatment, and to present possible future directions as the incidence of the disease is projected to persist in the future. Brief description of the state of knowledge: Alcoholic cardiomyopathy (ACM) is characterized by dilation, increased mass of the left ventricle, and reduced ejection fraction leading to end-stage heart failure. It is caused by ethanol’s direct toxicity on myocytes disturbing many different metabolic pathways. The result is a decrease in both systolic and diastolic function of the heart. The ACM development depends on factors such as genetics, gender, dietary factors and the dosage of ethanol consumption. The goal of the treatment is total alcohol abstinence, but the reduction of ethanol intake may also be beneficial. Patients should obtain a complete pharmacological treatment for heart failure. Summary: Ethanol overconsumption remains an unresolved problem, with the incidence of ACM projected to persist in the future, especially among patients with alcohol use disorder (AUD). Efforts for prevention, early detection, and effective treatment of ACM need to be established. A primary focus should be on treating AUD because it is the most effective way to halt the progression of the disease. Further research should focus on both asymptomatic and symptomatic patients with AUD to better define clinical manifestations, diagnostic approaches, and the most effective treatments for ACM.